Development and laboratory production of virus-like immune-stimulating complexes based on saponins and evaluation of their adjuvant potential using mice immunisation with influenza antigens - V. A. Evseenko; A. S. Gudymo; N. V. Danilchenko; S. V. Svyatchenko; O. S. Taranov; A. B. Ryzhikov (Биопрепараты: Профилактика, диагностика, лечение, 2022)
The COVID-19 pandemic has exacerbated the public’s need for effective vaccines. Consequently, significant financial support has been provided to developers of a number of innovative vaccines, including the vaccines with saponin-based adjuvants. In 2021, the World Health Organisation recommended Mosquirix, the first malaria vaccine, which contains a saponin adjuvant. An anti-covid vaccine by Novavax is in the approval phase. A promising approach to vaccine development is presented by the use of virus-like immune-stimulating complexes (ISCOMs) containing saponins and by the creation of combinations of ISCOMs with antigens. The aim of the study was to develop, produce and characterise virus-like immune-stimulating complexes based on saponins of Quillaja saponaria, as well as similar saponins of Russian-sourced Polemonium caeruleum. Materials and methods: The ISCOM adjuvants, Matrix-BQ and Matrix-BP, were produced using liquid chromatography and examined using electron microscopy. Balb/c mice were immunised intraperitoneally and intramuscularly with ISCOM-antigen preparations. Afterwards, the immunised animals were challenged with the influenza virus strain, A/California/4/2009(H1N1)pdm09, adapted and lethal to mice. The serum samples were examined using haemagglutination inhibition (HI) tests. Results: The authors produced the ISCOMs containing saponins of Quillaja saponaria and Polemonium caeruleum. After one intramuscular injection of either of the ISCOM-antigen preparations with 1 µg of each of A/Brisbane/02/2018 (H1N1) pdm09, A/Kansas/14/2017 (H3N2), and B/Phuket/3073/2013 haemagglutinin antigens (HAs), HI tests detected serum antibody titres to the corresponding antigens of ≥1:40. Two intramuscular injections of the ISCOM-antigen preparation containing 50 ng of each of the HAs and Matrix-BQ resulted in a protective response. In some animals, two intraperitoneal injections of ISCOM-antigen preparations resulted in the maximum antibody titre to the A/Kansas/14/2017 (H3N2) vaccine strain of 1:20,480. Two intramuscular injections of a test preparation containing 5 µg, 1 µg, 200 ng, or 50 ng of each of the HAs and Matrix-BQ or a control preparation containing 5 µg, 1 µg, or 200 ng of each of the HAs (commercially available vaccines) to the mice that were afterwards infected with the lethal influenza strain protected the experimental animals from death. Conclusions: The ISCOM-based preparations had high immunostimulatory activity in the mouse-model study. The presented results indicate the potential of further studies of ISCOM-based preparations in terms of both vaccine and immunotherapeutic development.